Construyendo seguridad para la manifestación de la sororidad desde #LasRespondonas - Diez, Illari (2020)
Nowadays, just as there is harassment and insecurity on social networking sites, these spaces can also be used by women for feminist activism and the sorority manifestation, for which, as has been seen in previous works, it is necessary security. In this sense, this article seeks to answer the following question: How is the feeling of security in #LasRespondonas—a Facebook group made up mostly of feminist women—for the manifestation of sorority built? It was found that the construction of the feeling of security in this group occurs thanks to three elements: the creation of a virtual community, the existence of an echo chamber, and the use of the platform tools together with the role of the moderators. In addition, security is necessary for the sorority manifestation in three moments: the verbalization of the problem, the sharing of information / interacting, and the meeting.